Measurement of "Tone" - A Technical Aspect
The purpose of this research work is to measure the Tone value. The recorded speech material consists of the extracted portion \`o of a syllable k\`o - (from kòṛa: `horse’) is used for measuring the momentum of the pitch in tone. A native speaker of Punjabi language from the Doab region (Punjab, India) has been selected for producing the word kòṛa: (the focus of this work is not on the sociolinguistic study of the data of the native speaker). On the basis of the simple graphical representation a formula has been applied for measuring the tone value of the language. This paper seeks to improve our competence regarding acoustic measurements of acoustic data through graphical representation. , number=1, journal=Journal of Informatics and Mathematical Sciences, author=Singh, Chander Shekhar, year=2010, month=May, pages=23–34